Pengembangan Bahan Ajar Digital E-Book Asik Nian Pada Pembelajaran IPAS Kelas IV SD - Henny Risnawaty Putri; M Taheri Akhbar; Susanti Faipri Selegi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This study aims to produce valid, practical, and effective digital e-book teaching materials on Indonesian Cultural Diversity in science and social studies learning for grade IV elementary school. This study uses the research and development method using the ADDIE model (analyze, design, development, implementation, evaluation). The results of the data analysis shows that the developed e-book is included in the "very valid" category based on the validation questionnaire sheet of experts (material experts, media experts, and language experts) with a validity value of 88.5%. The developed e-book is also included in the "very practical" category based on the results of the student response questionnaire with an average of 90.4% and the results of the practicality trial by filling out the posttest sheet with an average of 87.25% which is included in the "very practical" category. Based on these results, it shows that the e-book product can be used on the material on Indonesian cultural diversity in science learning for grade IV elementary school.